1983
DOI: 10.1109/jlt.1983.1072126
|View full text |Cite
|
Sign up to set email alerts
|

Broad-band ultrasonic sensor based on induced optical phase shifts in single-mode fibers

Abstract: Abstract-A broad-band ultrasonic sensor based on induced optical phase shifts in single-mode fibers is demonstrated over a frequency regime of 0550 MHz. In addition, a recently developed theory used to predict the magnitudes of acoustically induced strains in optical fibers is verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…This is the first account of a polarimetric optical fiber acoustic sensor. Further work on polarimetric optical fiber sensors has been undertaken by dePaula et al [64]- [66], and also by Chan et al [67], [70] with Price [68], and Brinch [69]. The work of Chan et al [67] describes a polarimetric optical fiber sensor based on acoustically induced birefringence in a polarization maintaining fiber.…”
Section: Optical Fiber Interferometersmentioning
confidence: 99%
“…This is the first account of a polarimetric optical fiber acoustic sensor. Further work on polarimetric optical fiber sensors has been undertaken by dePaula et al [64]- [66], and also by Chan et al [67], [70] with Price [68], and Brinch [69]. The work of Chan et al [67] describes a polarimetric optical fiber sensor based on acoustically induced birefringence in a polarization maintaining fiber.…”
Section: Optical Fiber Interferometersmentioning
confidence: 99%
“…, which we shall call the array receiving frequencies. From (2), it is also clear that the spectral amplitude of the signal detected by an M-element array increases by a factor of M at these frequencies when compared with single element detection. Consider an N-cycle ultrasonic toneburst of frequency ω 0 received by an M-element array receiver that is tuned to this frequency, i.e., the fiber array spacing is chosen such that δ = 2πc/ω 0 .…”
Section: G(ω) = Mh(ω)s(ω)mentioning
confidence: 99%
“…Their primary advantage over conventional strain gauges and thermocouples is that they are non-electrical devices that are also very compact. A number of researchers have also developed fiber optic sensors that are capable of detecting dynamic (high frequency) phenomena such as ultrasonic fields in a liquid [2], [3] or inside a solid structure [4], [5]. Fiber-optic ultrasound sensors have potential applications in smart structure technology [6], composite materials [7], materials processing industry [8], and medicine [9].…”
Section: Introductionmentioning
confidence: 99%
“…The principle of using a conventional single-mode fiber for ultrasound sensing has been known for some time [6]- [8]. It has been shown that when an ultrasonic wave in the megahertz range (in liquid) is incident normally upon a single-mode fiber, the fiber becomes anisotropic so that the two orthogonal linear polarizations of light in the fiber encounter different refractive indexes, and hence, propagate at different velocities [6], [8].…”
Section: Introduction T Present the Most Widely Used Device For Smentioning
confidence: 99%
“…It has been shown that when an ultrasonic wave in the megahertz range (in liquid) is incident normally upon a single-mode fiber, the fiber becomes anisotropic so that the two orthogonal linear polarizations of light in the fiber encounter different refractive indexes, and hence, propagate at different velocities [6], [8]. A polarimetric ultra- CHAN, AND JAMES L. GARDNER sonic sensor based on the detection of such induced birefringence in a single-mode fiber has been demonstrated [7].…”
Section: Introduction T Present the Most Widely Used Device For Smentioning
confidence: 99%